The Influence Of Servıce Fıltures, Promotıons, Convenıence And Prıce On Usıng Decısıons (Case Study on E-wallet Dana Products in Madiun City) - Dian Citaningtyas Ari Kadi; Muhammad Awwalul Verdi Firdausi (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Modern life is increasingly developing, causing technology to become more advanced, the use of money is becoming easier and more sophisticated with the existence of e-wallets, meaning people don't need to carry cash for any payment, which is easier by just carrying a digital wallet. The aim of this research is to empirically prove the influence of service features, promotions, convenience and price on usage decisions. This research was conducted on e-wallet users, especially in Madiun City, using a purposive sampling method with certain criteria and obtained 384 respondents. The research was conducted for 5 months. This research method uses a quantitative approach using IBM SPSS Statistics version 26. The results of this research are that the Service Feature variable has a significant influence on usage decisions, promotion has a significant influence on usage decisions, convenience has a significant influence on usage decisions, and it can also be seen that price has an influence significant impact on the decision to use Dana's e-wallet in Madiun City